Resposta :
Explicação passo-a-passo:
[tex]a)(x {}^{4} ) {}^{ - 3} = x {}^{4. - 3} = x {}^{ - 12} [/tex]
[tex]b)( - 4 {}^{2} ) {}^{3} = ( - 4) {}^{2.3} = ( - 4) {}^{6} [/tex]
[tex]c)(4 \times 5 {}^{1} \times 6) {}^{3} = 4 {}^{3} \times 5 \times 6 {}^{3} [/tex]
[tex]d)(5 {}^{ - 2} .5 {}^{3} ) {}^{5} = (5 {}^{ - 2 + 3} ) {}^{5} = 5 {}^{5} [/tex]
Resposta:
[tex]\sf{a)(x {}^{4}) {}^{ - 3} } = x {}^{4. - 3} = x { }^{ - 12} [/tex]
[tex]\sf{b)( - 4 {}^{2} ) { }^{3} } = ( - 4) {}^{2.3 } = ( - 4) {}^{6} [/tex]
[tex]\sf{c)(4 x5 {}^{1} x6) {}^{3} } = 4 {}^{3} x5x6 {}^{3} [/tex]
[tex]\sf{d)(5 {}^{ - 2} }.5 {}^{3} ) {}^{5} = (5 {}^{ - 2 + 3} ) {}^{5 } = {5}^{5} [/tex]
Explicação passo-a-passo: